Upaya Peningkatan Literasi Sains Melalui Game Edukasi untuk Peserta Didik Sekolah Dasar Kelas Rendah di Desa Kesetnana: Increasing Science Literacy through Educational Games for Primary School Students in Low-Income Desa Kesetnana - Mellu, Ruth Novi Kornalia; Gella, Netty Julinda Marlin; Laos, Landiana Etni; Billik, Marthisa Olivia; Baun, Ermes Benediktus; Nenoliu, Nelson (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The aim of this community service activity is to enhance the scientific literacy skills of lower-grade students in Kesetnana village through educational game-based lessons. The activity is conducted in several stages, including planning, preparation, implementation, evaluation, and reporting. The outcome of this initiative is the development of educational game media and its utilization in the teaching process, resulting in a significant increase in scientific literacy skills of over 65%. Additionally, students' interest in learning has risen by 68.8% according to indicators of learning motivation, demonstrating their positive response to the educational game-based approach. Therefore, efforts to promote scientific literacy among lower-grade elementary school students in Kesetnana village can be effectively carried out through regular lesson activities over a three-week period, leading to improved scientific literacy skills and increased learning motivation.